Optimizing the Targeting of Mouse Parvovirus 1 to Murine Melanoma Selects for Recombinant Genomes and Novel Mutations in the Viral Capsid Gene - Marr, Matthew; D’Abramo, Anthony; Pittman, Nikea; Agbandje-McKenna, Mavis; Cotmore, Susan; Tattersall, Peter (Viruses, 2018)
Combining virus-enhanced immunogenicity with direct delivery of immunomodulatory molecules would represent a novel treatment modality for melanoma, and would require development of new viral vectors capable of targeting melanoma cells preferentially. Here we explore the use of rodent protoparvoviruses targeting cells of the murine melanoma model B16F10. An uncloned stock of mouse parvovirus 1 (MPV1) showed some efficacy, which was substantially enhanced following serial passage in the target cell. Molecular cloning of the genes of both starter and selected virus pools revealed considerable sequence diversity. Chimera analysis mapped the majority of the improved infectivity to the product of the major coat protein gene, VP2, in which linked blocks of amino acid changes and one or other of two apparently spontaneous mutations were selected. Intragenic chimeras showed that these represented separable components, both contributing to enhanced infection. Comparison of biochemical parameters of infection by clonal viruses indicated that the enhancement due to changes in VP2 operates after the virus has bound to the cell surface and penetrated into the cell. Construction of an in silico homology model for MPV1 allowed placement of these changes within the capsid shell, and revealed aspects of the capsid involved in infection initiation that had not been previously recognized.